Novel drying additives and their evaluation for self-flowing refractory castables. Issue 3 (15th February 2020) - Bezerra, B.P.; Luz, A.P.; Pandolfelli, V.C.
Abstract: The drying step of dense refractory castables containing hydraulic binders is a critical process, which usually requires using slow heating rates due to the high explosion trend of such materials during their first thermal treatment. Thus, this work investigated the performance of alternative additives to induce faster and safer drying of self-flowing high-alumina refractory castables bonded with calcium aluminate cement (CAC) or hydratable alumina (HA). The following materials were analyzed for this purpose: polymeric fibers, a permeability enhancing compound (RefPac MIPORE 20) and an organic additive (aluminum salt of 2-hydroxypropanoic acid). The drying behavior and explosion resistance of the cured samples were evaluated when subjecting the prepared castables to heating rates of 2, 5 or 20 °C/min and the obtained data were then correlated to the potential of the drying agents to improve the permeability and mechanical strength level of the refractories at different temperatures. The collected results attested that the selected additives were more efficient in optimizing the drying behavior of the CAC-bonded compositions, whereas the HA-containing castables performed better when the aluminum-based salt was blended with a small amount of CAC (0.5 wt%), which changed the binders hydration reaction sequence and optimized the permeability level of the resulting microstructure. Consequently, some of the designed compositions evaluated in this work showed improved drying behavior and no explosion was observed even during the tests carried out under a high heating rate (20 °C/min).